Looking to eat Nokia's lunch [3G cell phones]. - Blau, J. (IEEE spectrum)
Microsoft and Intel want to create a template for third-generation wireless devices, but they're not alone. This Microsoft-Intel initiative sets the stage for a big battle with the leading manufacturers of mobile phones. The present paper discusses the talks being held between several companies and the prospects for collaborations